Can structural or functional changes following traumatic brain injury in the rat predict epileptic outcome?. Issue 7 (29th May 2013) - Shultz, Sandy R.; Cardamone, Lisa; Liu, Ying R.; Hogan, R. Edward; Maccotta, Luigi; Wright, David K.; Zheng, Ping; Koe, Amelia; Gregoire, Marie‐Claude; Williams, John P.; Hicks, Rodney J.; Jones, Nigel C.; et al.
Summary Purpose Posttraumatic epilepsy (PTE) occurs in a proportion of traumatic brain injury (TBI) cases, significantly compounding the disability, and risk of injury and death for sufferers. To date, predictive biomarkers for PTE have not been identified. This study used the lateral fluid percussion injury (LFPI) rat model of TBI to investigate whether structural, functional, and behavioral changes post‐TBI relate to the later development of PTE. Methods Adult male Wistar rats underwent LFPI or sham injury. Serial magnetic resonance (MR) and positron emission tomography (PET) imaging, and behavioral analyses were performed over 6 months postinjury. Rats were then implanted with recording electrodes and monitored for two consecutive weeks using video–electroencephalography (EEG) to assess for PTE. Of the LFPI rats, 52% (n = 12) displayed spontaneous recurring seizures and/or epileptic discharges on the video‐EEG recordings. Key Findings MRI volumetric and signal analysis of changes in cortex, hippocampus, thalamus, and amygdala, 18F‐fluorodeoxyglucose (FDG)–PET analysis of metabolic function, and behavioral analysis of cognitive and emotional changes, at 1 week, and 1, 3, and 6 months post‐LFPI, all failed to identify significant differences on univariate analysis between the epileptic and nonepileptic groups. However, hippocampal surface shape analysis using large‐deformation high‐dimensional mapping identified significant changes in the ipsilateral hippocampus at 1 week postinjury relative to baseline that differed between rats that would go onto become epileptic versus those who did not. Furthermore, a multivariate logistic regression model that incorporated the 1 week, and 1 and 3 month 18F‐FDG PET parameters from the ipsilateral hippocampus was able to correctly predict the epileptic outcome in all of the LFPI cases. As such, these subtle changes in the ipsilateral hippocampus at acute phases after LFPI may be related to PTE and require further examination. Significance These findings suggest that PTE may be independent of major structural, functional, and behavioral changes induced by TBI, and suggest that more subtle abnormalities are likely involved. However, there are limitations associated with studying acquired epilepsies in animal models that must be considered when interpreting these results, in particular the failure to detect differences between the groups may be related to the limitations of properly identifying/separating the epileptic and nonepileptic animals into the correct group.